The life and work of Benjamin Tyamzashe: a contemporary Xhosa composer - Hansen, Deirdre Doris (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 1968)
In this study I have tried to show what Tyamzashe has achieved without the solid musical training any composer worthy of the name should undergo. I have also tried to show the forming of his own musical style under the impact of outside influences. This study is therefore not to teach one anything new, but simply to communicate the results of three years research. In it I have attempted to set the scene in which Tyamzashe's life unfolded itself under the influences of people and circumstances. In doing so I have tried to bear in mind the main theme - Tyamzashe himself. My problem was not so much what to include but what to leave out; thus I have not provided the scene with a detailed background. The section on missionary contact is necessary for an understanding of the great changes brought about by culture contact, as well as for putting Tyamzashe into his historical background. I have also stressed Lovedale because musical change as exemplified in the music of early Bantu converts was centralized there. Finally, the thesis of this study is: despite the changes introduced into Bantu music by culture contact, one perceives, in the works of Tyamzashe, the beginnings of a new pattern of integration. p. 2-3.
Keywords: Tyamzashe, Benjamin, 1890 -- Criticism and interpretation; Xhosa (African people) -- Music; Hymns, Xhosa; Composers, Black -- South Africa